2000
DOI: 10.1007/s002160050053
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace elements in marine plankton by inductively coupled plasma mass spectrometry (ICP-MS)

Abstract: A method has been developed for the determination of 23 elements in marine plankton in which inductively coupled plasma (ICP) source mass spectrometry (MS) was used to quantify the elements in the solution after digestion in a mixture of hydrofluoric and nitric acids in sealed PTFE vessels in a microwave field. The procedure was validated by the analysis of a standard reference soil (SRM 2709 San Joaquin Soil) and a standard reference fresh water plankton (CRM 414). The method was applied to the analysis of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…To reduce the matrix effect caused by silicon (Arslan et al 2000), hydrofluoric acid was not applied in the digestion step. After diluting the digested solution to 10 mL with Milli-Q water and removing the filter, the solution was centrifuged to remove any particulate residues.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the matrix effect caused by silicon (Arslan et al 2000), hydrofluoric acid was not applied in the digestion step. After diluting the digested solution to 10 mL with Milli-Q water and removing the filter, the solution was centrifuged to remove any particulate residues.…”
Section: Methodsmentioning
confidence: 99%
“…One challenge is the choice of sample dissolution technique in which the various mercury species are to be solubilised as the inorganic mercury 2+ ion. 22,24 It is well known that mercury is easily volatilised, so samples cannot be heated to high temperatures without analyte loss and this complicates the use of microwave-assisted digestion and hotplate digestions.…”
Section: Preparation Of Solutions and Standardsmentioning
confidence: 99%
“…Plankton are mainly composed of organic material, and to some extent contain silicon which is an essential element for planktonic growth [39,40]. Thus, we investigated the performance of dilute HF as a suspension medium for plankton slurries in addition to water and dilute HNO 3 .…”
Section: Effect Of Extraction Mediummentioning
confidence: 99%
“…In the analysis of freshwater plankton for method validation, the slurry concentration was not modified and kept constant at 1% m/v since the concentration of Pb was relatively high. For marine plankton samples, ICP-MS analysis [40] revealed that content of Pb was at least an order magnitude lower than in freshwater plankton; therefore, slurries were made in 3% m/v range to achieve accurate determination.…”
Section: Slurry Concentrationmentioning
confidence: 99%
See 1 more Smart Citation